Model Anggaran Perusahaan berbasis Laporan Keuangan - Arwan Gunawan; Jouzar Farouq Ishak (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The fundamental problem in corporate budgeting in Indonesia is that there is no transparency addressed to stakeholders outside the internal conditions of management. So that in realizing the company budget, it is enough for those interested parties to only trust the audited financial statements. Even though the audited financial report is prepared by an Independent Auditor, it is still necessary to make preventive efforts by investors to anticipate various possible changes at any time. If investors anticipate it at the end of the company's bookkeeping period, it can be said to be “too late”. The company budget model that is built and developed by the company is inseparable from the company's financial statements that have been audited in previous periods. Therefore, it is necessary to conduct a study on how the financial statement-based corporate budget model is made for managerial decision making and the optimization of firm value (value of the firm). Descriptive research has been conducted to describe the company budget model based on financial statements. The results of descriptive research indicate that a financial statement-based company budget model can be formed. The next research step must be made an application of a company budget model based on financial statements.